Who's the Fairest of Them All? Evidence from Closed-End Funds - Lawrence, Alastair; Siriviriyakul, Subprasiri; Sloan, Richard G (The Accounting Review, 2016)
ABSTRACT Prior research examining the ASC 820 fair value hierarchy concludes that Level 3 fair value measurements are significantly less value-relevant than Level 1 and Level 2 fair value measurements. We reevaluate this conclusion using the closed-end fund setting, in which fair value measurements are available for substantially all assets. Contrary to prior research, we find that Level 3 fair values are of similar value relevance to Level 1 and Level 2 fair values. Our findings suggest that the results in previous research are attributable to correlated omitted variable bias arising from the absence of fair value data for most assets. JEL Classifications: M41; G12; G29. Data Availability: Data are publicly available from sources identified in the article.